Pembangunan Aplikasi Pengenalan Rempah-Rempah Indonesia Menggunakan Augmented Reality Berbasis Android - Sigit Gunawan; Yulius Denny Prabowo (UNIVERSITAS KALBIS, 2022)
The objective of this research is to develop an augmented reality-based Android application for the promotion of Indonesian spices. This application was created using the Multimedia Development Life Cycle (MDLC), which consists of the following stages: Concept, Design, Material Collection, Manufacture, Testing, and Distribution. Developing an application utilizing Unity and Vuforia software. Then, in the design phase of creating application applications, Blender and Adobe Photoshop are utilized. The application utilizes the Black box test and User Experience during the testing phase. This research led to the development of an application called REMPAHAR that provides users with information on Indonesian spices and 3D spice object forms.